THE INFLUENCE OF SOCIAL SUPPORT ON THE RESILIENCE OF DRUG PRISONERS AT THE CLASS IIA MADIUN YOUTH CORRECTIONAL INSTITUTION - Tajuddin, Fauzan Shidqi; Wibowo, Padmono (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to determine the effect of social support on the resilience of narcotics prisoners at the Class IIA Madiun Youth Correctional Institution. The research method used is quantitative research with survey design. The sample in the study was narcotics prisoners who had completed rehabilitation with a total of 80 people. This study used a sampling technique with simple random sampling. Data obtained from the results of distributing questionnaires. Data analysis using univariate analysis, normality test, simple linear regression, significance test and determination test using IBM SPSS 27 software. The results of the analysis showed that there is an effect of social support on the resilience of prisoners. The results of the determination test indicate that the social support variable has an influence of 44.1% on the resilience variable, while the remaining 55.9% is influenced by other variables not explained in this study. Keywords: Social Support; Resilience; Prisoners